2017
DOI: 10.15520/ijcrr/2017/8/10/329
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Foreign Body: A Retrospective Study

Abstract: Abstract:Background: Nasal foreign bodies are a frequent accident to otolaryngologist especially in young children. They are generally harmless and can be managed easily in outpatient department but may become life threatening if it is overlooked or attempt at removal by unskilled hand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…A small percentage, 1-2% of patients, present with foreign bodies in both nasal cavities (6)(7)(8) and in 0.4% also with an auricular foreign body (6) . Most patients present within one week after foreign body insertion (1,7) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small percentage, 1-2% of patients, present with foreign bodies in both nasal cavities (6)(7)(8) and in 0.4% also with an auricular foreign body (6) . Most patients present within one week after foreign body insertion (1,7) .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, proper examinations should be carried out, including the contralateral site of the nose and ear examinations, to avoid missing any significant findings. Most studies show that foreign bodies are found more frequently in the right side of the nasal cavities (6)(7)(8) . This is partly due to the fact that most people are right-handed, as in our presented case.…”
Section: Discussionmentioning
confidence: 99%